(untitled) (Research, Society and Development, 2021)
The health care of trans women and trans men has many consequences in relation to their specificities, so it is necessary that the construction of this knowledge occurs in the graduation of the professional nurse in order to analyze, under the light of the Methodology of Resolution of Situations- The problem is the effectiveness of the world café technique for the construction of knowledge of nursing students in the face of problem solving regarding care for transsexual, transvestite and transgender people from a pedagogical workshop. Method: Qualitative approach research, with characteristic: field, exploratory and thematic study carried out in February 2020, through a workshop in the World Café model, which is a technique of collaboratively generating ideas. The results presented here are part of an excerpt of the dissertation for the Master’s course. Data were analyzed following the assumptions of discourse analysis proposed by Laurence Bardin and their results were grouped into analysis categories: I – Health education; II- Competences; III - Professional ethics. The research demonstrates the importance of building knowledge about the health care of Trans people, even in the undergraduate and research courses, in order to promote quality health care, comprehensiveness, equality and equity for trans men and women.